Social Security, Labor Supply and Health of Older Workers: Quasi-Experimental Evidence from a Large Reform - Itay Saporta-Eksten; Ity Shurtz; Sarit Weisburd (Institute of Labor Economics (IZA), 2020)
We study the effects of public pension systems on the retirement timing of older workers and, in turn, the health consequences of delaying retirement by those workers. Causal inference relies on a social security reform in Israel that shifted payments from husbands to their (non-working) wives, thereby substantially reducing the implied tax on the husband's employment while keeping overall household wealth constant. Using administrative social security data, we estimate extensive-margin labor supply elasticities w.r.t. the average net-of-tax rate of about 0.43 for men over 65. Using the reform to instrument for employment, we find that working an additional full year at old age decreases longevity. This mortality effect occurs after age 75 and is driven by workers holding blue-collar jobs. Finally, we evaluate the effect of the reform on earnings. The results imply a small value for an additional year of life, suggesting that workers underestimate the health cost of employment at older ages.
Keywords: H55; J14; J17; J22; J26; 330; labor supply; social security; tax reform; health; mortality